Causes of sudden death in the young — Cardiac and non-cardiac. (June 2017) - Lang, Janet E; Pflaumer, Andreas; Davis, Andrew M
Abstract: The spectrum of causes of sudden death in the young is broad and varied. Sudden death in a young person is always a tragedy, more so because many sudden deaths are potentially preventable. Clinicians caring for the young need to be familiar with the causes to allow precise diagnosis and focused management. Paediatric Cardiologists need to be aware of non-cardiac causes and similarly Paediatricians need to be aware that there are a wide spectrum of cardiac causes that may be difficult to diagnose. In addition many of the causes of cardiac death such as "electrical myopathy" and myocardial disease are inherited mandating a thorough and complete search within the extended family. Highlights: The causes of sudden death in the young are broad and varied. Many cases of sudden death are potentially preventable Many causes of cardiac death are inherited mandating a thorough search within the extended family.